The role of invasive and non-invasive imaging technologies and calcium modification therapies in the evaluation and management of coronary artery calcifications - Wopperer, Samuel B.; Kotronias, Rafail; Marin, Federico; Benenati, Stefano; Della Mora, Francesco; Portolan, Leonardo; Banning, Adrian P.; De Maria, Giovanni Luigi (Frontiers in Cardiovascular Medicine, 2023)
The treatment of coronary artery disease (CAD) has advanced significantly in recent years due to improvements in medical therapy and percutaneous or surgical revascularization. However, a persistent obstacle in the percutaneous management of CAD is coronary artery calcification (CAC), which portends to higher rates of procedural challenges, post-intervention complications, and overall poor prognosis. With the advent of novel multimodality imaging technologies spanning from intravascular ultrasound to optical coherence tomography to coronary computed tomography angiography combined with advances in calcium debulking and modification techniques, CACs are now targets for intervention with growing success. This review will summarize the most recent developments in the diagnosis and characterization of CAC, offer a comparison of the aforementioned imaging technologies including which ones are most suitable for specific clinical presentations, and review the CAC modifying therapies currently available.